Analysis of the Success of the Grab Application from the Perspective of Palembang City Users Using the DeLone and McLean Approach - Nabilah Putri Risa (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2024)
Information systems play a crucial role in facilitating business operations across various sectors, including transportation. Grab, a Singapore-based digital transportation platform, offers multiple services such as ride-hailing, courier delivery, and food delivery. This study aims to analyze the success of the Grab application from the perspective of community users in Palembang City using the DeLone and McLean Information System Success Model. The study evaluates six variables Information Quality, System Quality, Service Quality, Use, User Satisfaction, and Net Benefits to identify key factors influencing the application's success and propose strategic recommendations to enhance performance. The study employed a quantitative descriptive approach using a structured questionnaire distributed to 120 Grab users in Palembang. Data were analyzed using the Statistical Product and Service Solutions (SPSS) software through t-tests and F-tests. The findings indicate that Service Quality, Intention to Use, and Actual Use significantly affect user satisfaction. These factors are crucial in determining the overall success of the Grab application.